2010
DOI: 10.1016/j.gaitpost.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The test–retest reliability of centre of pressure measures in bipedal static task conditions – A systematic review of the literature

Abstract: Conclusions: The studies reviewed show that bipedal static COP measures may be used as a reliable tool for investigating general postural stability and balance performance under specific conditions. Recommendations for maximizing the reliability of COP data are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
487
4
22

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(536 citation statements)
references
References 49 publications
23
487
4
22
Order By: Relevance
“…The study of the ICCs on four posturo-stabilometric parameters in six different mandibular/visual conditions calculated on two distanced sessions, demonstrated that the examination with the force plate not only has a good intrasession reliability, as Bauer et al (2010), Ruhe et al (2010), Corriveau et al (2000) said, but also has a good intersession reliability.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The study of the ICCs on four posturo-stabilometric parameters in six different mandibular/visual conditions calculated on two distanced sessions, demonstrated that the examination with the force plate not only has a good intrasession reliability, as Bauer et al (2010), Ruhe et al (2010), Corriveau et al (2000) said, but also has a good intersession reliability.…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature on intrasession variability (Bauer et al, 2010;Ruhe et al, 2010), focused only on the precision and the accuracy of the instrument and the variation of the phenomena, suggesting the utility of the instrument in a diagnostic setting but limited to a single test session. It is still not clear if this instrument could be useful during the follow-up analysis of a therapeutic plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The software Balance Clinic (AMTI Inc.) was used for signal recording (Scoppa et al 2013). The reliability coefficient was described elsewhere (r ≥ 0.75) (Ruhe 2010).…”
Section: Static and Dynamic Balancementioning
confidence: 99%
“…The data acquisition was initiated 3 seconds after starting the testing procedure and was done in a total of 3 trials (Pinsault & Vuillerme, 2009;Ruhe et al, 2010). All individuals were asked to stand as still as possible (Zok et al, 2008), with the support base aligned at shoulder width, keeping their arms by their sides and to focus on a target 2 meters away and at eye level during 30 seconds (Le Clair & Riach, 1996).…”
Section: Data Collectionmentioning
confidence: 99%